Multivessel Coronary Artery Thrombosis Accompanying Acute Myocardial Infarction: A Case Report (Annals of Medical Research, 2021)
None
Keywords: Myocardial Infarction; Coronary Artery Disease; Multivessel Coronary Trombosis.